2022
DOI: 10.14740/jocmr4793
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Tapered Steroid Regimen When Used to Treat Acute Borderline Cellular Rejection After Kidney Transplant: A Single-Center Experience

Abstract: Background: Treatment of acute borderline cellular rejection (BCR) after kidney transplant has shown mixed results with no consensus on the necessity and modality of interventions. Methods:The emphasis of our study was to assess the histopathologic response when BCR of kidney transplant is being treated with rapid steroid regimen. We analyzed all diagnosed acute BCR between 2018 and 2020. Patients were divided to a treatment responder group (RG) and non-responder group (NRG). All diagnosed BCR were treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…It was found that persistent acute BCR occurred in 63 out of 91 patients despite treatment; thus, only a 31% response rate was achieved. There were no differences between the two groups in terms of induction therapy with alemtuzumab, thymoglobulin and basiliximab [65].…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…It was found that persistent acute BCR occurred in 63 out of 91 patients despite treatment; thus, only a 31% response rate was achieved. There were no differences between the two groups in terms of induction therapy with alemtuzumab, thymoglobulin and basiliximab [65].…”
mentioning
confidence: 80%
“…The BCR therapeutic approach is still a subject of ongoing discussion, which regard mostly its modality, regimen and efficacy [54]. Besides the administration of methylprednisolone and prednisone in a rapid steroid regimen, the induction protocol is based on basiliximab, alemtuzumab or ATG [65].…”
Section: Borderline Rejectionmentioning
confidence: 99%